ASPECTS AND PROBLEMS OF NATURAL SELF-CLEANING POTENTIAL EVALUATION FOR URBANIZED ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The article deals with the concept of natural self-cleaning potential. It contains a description of available urbanized environment natural self-cleaning potential evaluation methodics and specific methods employed. Groups of criteria, producing different influence on self-cleaning geopotential were distinguished. Each criterion was evaluated by grades – related with parameters of impact factors – taking into consideration its rank in the general system of evaluation.